Analysis of the Structure of the Georgian Economy - Cardenete Flores, Manuel Alejandro; Delgado López, María del Carmen (Papeles de Europa, 2011)
This paper analyzes the economic structure of the Georgian economy by 2007. Using the Social Accounting Matrix of this country for that particular year, authors analyze the key sectors of the economy. There can be found an accounting decomposition of multipliers in their three effects (direct, indirect and induced), and finally, the analysis of the reaction of different productive sectors in the region to the transfer of funds received by the USAID and the distribution of income and expenditure of Georgians consumers is run. The results show the most important sectors of the country, among them are to be included: Agriculture, Manufacturing and Trade, as well as the sectors of minor impact and importance which are in the case Mining, Education and Government Institutions.